USING VIRTUAL REALITY PLATFORMS FOR COLLABORATIVE LEARNING - Sarsimbayeva С.М.; Mukasheva М.У.; DUZBAYEVA Г.Б. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
Abstract. The article discusses the issues of the development of the methodological basis of collaborative learning using computer systems. The advantages of virtual reality technology for the development of collaborative learning ideas are shown. The issues of organizing collaborative training with the use of a virtual reality environment are outlined, examples of recent works showing the use of the Open Simulator platform are given. The possibilities of the well-known virtual reality platform Rumii are shown, an example of the application of the virtual reality platform Rumii for the organization of collaborative training is given. The authors conclude that the use of virtual reality for collaborative learning gives good results. To organize classes for collaborative learning using virtual reality technology, online virtual reality platforms can be used, such platforms as Open Simulator, Rumii as a virtual educational environment in training enhance the possibilities of collaborative learning. The article is useful for educational institutions, teachers and researchers seeking to introduce innovative solutions into the educational process.